Development of computer-aided materials and manufacturing process selection software using Boothroyd-Dewhurst methodology - Sulong@Zakaria, Zaeime (2010)
The interest of this thesis is about the application system developed by selection in engineering materials and manufacturing process using the Boothroyd Dewhurst methodology as a main guidance. The implementation of this application gives opportunity to the designer to improve the best materials by using the best process during the early steps of product design. A prototype application system called CAM-MaPS and the uses of Visual Basic software had implemented the proposed methodology. By selecting the parts on knowing the common materials and process, in which to produce will be compared to the future result by using the CAM-MaPS for optimization.